TLTC, a T5 exonuclease–mediated low-temperature DNA cloning method - Yu, Fang; Li, Xia; Wang, Fei; Liu, Yang; Zhai, Chao; Li, Wenqiang; Ma, Lixin; Chen, Wanping (Frontiers in Bioengineering and Biotechnology, 2023)
Molecular cloning is used in a wide variety of biological and medical research.Here, we developed a rapid and efficient DNA assembling method for routine laboratory work.We discovered the cleavage speed of T5 exonuclease is approximately 3 nt/min at 0 ℃, hence, developed a T5 exonuclease mediated low-temperature sequence-and ligation-independent cloning method (TLTC). Two homologous regions of 15-25 bp compatible with the ends of the vector backbones were introduced into the inserts through PCR.Approximately 120 fmol of insert and linear vector were mixed at a molar ratio of approximately 3:1 and treated with 0.5 U of T5 exonuclease at 0 ℃ for 5 min. And then, the mixture was transformed into E. coli to generate recombinant plasmids. Single and multi-segments can be assembled efficiently with TLTC.For single segment , the overall cloning efficiency is above of 95%. Moreover, extra nucleotides in the vectors can be removed during TLTC. In conclusions, an extremely simple and fast DNA cloning/assembling method was established in the present study. This method facilitate routine DNA cloning and synthesis of DNA fragments.